Coming to Terms with Inter-sectarian Love Courtship and Marriage in Haider’s How It Happened - Qamar, Sadia; Shaheen, Aamer (Annals of Human and Social Sciences, 2024)
The paper closely reads Shazaf Fatima Haider’s How It Happened (2012) following the observations made by Simone de Beauvoir in her seminal work The Second Sex (1953). Beauvoir, talking about marriages, favours love marriages over arranged marriages. Focusing on the characters of Dadi and her two grandchildren siblings: Haroon and Zeba, the novel depicts the social picture of Pakistani society vis-à-vis the settlements of love marriages and to top that even inter-sectarian marriages – a phenomena yet quite rare in Pakistani society. The dramatic countering positions, on the issues of marriage, between Dadi and her grandchildren (Older/Traditional Generation versus Younger/Modern Generation) help showcase the familial complications and provide the readers a vantage point to reconsider their social understandings through the prism of Haider’s novel. Haider, through the turns of events within a Shia Syed household, brings to fore, though in a comedic vein, the gradual progress in rigid traditional families for accepting the younger generation’s stances of inter-sectarian love courtship and marriage enabling them to overcome the rigid positions vis-à-vis making matches that the older generations as those of Dadi’s could not come to terms with.